Maternal and host effects mediate the adaptive expansion and contraction of the microbiome during ontogeny in a holometabolous, polyphagous insect. (10th February 2023) - Jose, Polpass Arul; Yuval, Boaz; Jurkevitch, Edouard
Abstract: Polyphagous, holometabolous insects adapt to rapid diet shifts imposed by their ecology and their life cycle. One shift is linked to development, as larvae and adults usually dwell and feed in different environments, using different resources. The second is caused by changes in larval hosts, often occurring at each generation. Studies show that the insect's microbiome also changes in relation to development and larval host. However, parental and larval host contributions to its structure and trans‐generational dynamics remain uncharted. We investigated the sources of variation of the microbiome of the highly polyphagous Mediterranean fruit fly by tracking microbiome structure and its potential functional impact in fly lineages over generations and fruit host shifts, using 16S rRNA gene amplicon single variant analysis. Bacterial community alpha‐diversity expanded and contracted cyclically in a life stage‐dependent manner with the mothers' microbiome community 'resetting' to the same structure across generations. Expansion occurred at the larval stage, while alpha‐diversity decreased in tenerals, and significantly in mothers. In contrast, richness was highest in mothers, with rare taxa expanding in larvae depending upon fruit type. Metabolic predictions using PICRUSt pointed to increased metabolism of vitamins in mothers, and of aromatic compouds in larvae and tenerals, while indicator species analysis suggested fruit host composition‐dependent potential functional adaptations. Our data indicate lineage, fruit host and their interactions as the main sources of microbiome variation and provide examples of possible metabolic developmental and ecological adaptations. Taken together, these data support the hypothesis that microbiome diversity and microbiome‐driven local adaptations act as a mechanism sustaining polyphagy. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.